The influence of audio-visual interactions on the annoyance ratings for wind turbines. (1st January 2018) - Szychowska, Malina; Hafke-Dys, Honorata; Preis, Anna; Kociński, Jędrzej; Kleka, Paweł
Graphical abstract: Highlights: Wind turbines are not more annoying than other sources at the same sound level. Vision affects annoyance differently for natural samples and for transportation or wind turbines samples. Wind turbine recognition might increase the annoyance. Presence of wind turbines increases the annoyance of the environmental samples. Audio-visual wind turbines samples are rated similarly to transportation samples. Abstract: Annoyance has a negative influence on health and well-being, and over a longer time, it can increase the risk of stress, sleep disturbance, obesity and even heart attacks. The aim of this paper was to investigate the influence of audio-visual information on the assessment of annoyance caused by wind turbines. Seven soundscapes and seven landscapes were presented to 44 participants in an anechoic chamber with an ambisonic set up of 25 + 1 loudspeakers, and a large sound-permeable screen for visual presentation. First, participants were presented with auditory samples and asked to rate the noise annoyance on the ICBEN scale. Subsequently, they were asked to identify the sound sources. Second, participants were presented with visual samples and asked to rate their annoyance. Last, participants were presented with audio-visual mixes and again asked to rate their annoyance. The obtained results suggest that sound level of auditory presentation was the most influential factor in the annoyance assessment. The second most influential factor was the presented visual sample, and the least influential factor was the presented audio samples. Recognition of wind turbines tended to increase the annoyance ratings of the small wind turbines audio sample. Moreover, the participants who recognized the wind turbine also tended to rate the transportation samples as more annoying, but not the natural-like samples. In general, the audio and audio-visual samples of wind turbines were assessed similarly to the transportation samples, but not to the natural-like samples.